Reliability of Jacket Platforms in Malaysian Waters Sensitivity Study using Pushover Analysis - Kurian, V.J. (2013)
Abstract—Issues regard to continued usage of aging jacket platforms and Enhanced Oil Recovery (EOR) affecting the aged fixed jacket platforms owned by PETRONAS in Malaysian waters was studied. Pile buckling together with lateral soil failure and lengthy/ monotonous reliability analysis were identified as the core research issues related to the problem statement. SACS software was used on existing jacket platform structural model to carry out pushover analyses. Reserve Strength Ratio (RSR) was obtained through different combinations of dead, live, and storm loads. It was found that live load combinations had insignificance on the RSR value compared to variation in storm directions. RSR values from directional loads and resistance are very much volatile and significant. The response of the pile foundation to the environmental load is strongly affected by pile soil interaction. Since the development of p-y curve represents the pile foundation and soil structure interaction, it was used to model the soil resistance to the pile movements and the results obtained were analyzed. Collapse analysis with PSI yields lower RSR compared to an analysis without PSI. Inclusion of PSI (pile soil interaction) increased the RSR value in the range of 5.6% to 50.1%. A trend called slender column and truss system effects were introduced for the pushover analysis with and without PSI, respectively. Sensitivity study was in agreement with failure mechanisms experienced in the pushover analysis. Index Terms — Reliability, Jacket Platforms, RSR, p-y curve, pile-soil interaction.